THE EFFECT OF THE MEMORY STRENGTH STRATEGY ON DEDUCTIVE THINKING AMONG INTERMEDIATE SCHOOL STUDENTS IN MATHEMATICS - Sarah Abdel Salam Ibrahim (Scholars Digest Publishing, 2024)
The aim of the current research is to know the effect of the memory strength strategy on deductive thinking among intermediate school students in mathematics, where the researcher followed the experimental approach, as the research sample was represented by the second intermediate grade students in (Al-Karkh Girls Secondary School), with (56) students for the academic year (2023_2024) AD, distributed into two groups, one of which was experimental and studied according to the (memory strength) strategy, consisting of (28) students, and the other was a control group that studied according to the usual method, consisting of (28) students, and the two research groups were rewarded with (chronological age calculated in months, previous achievement in mathematics, previous knowledge test, and intelligence test), and prepared The researcher tested deductive thinking skills consisting of (16) objective paragraphs. After verifying the validity of the test and the reliability coefficient was acceptable, the equation (Kuder-Richason_20) was used to find it (0.73). After the experiment was completed, the deductive thinking test was applied to both research groups. After using statistical methods for the research, statistical methods resulted in a statistically significant difference between the two groups in favor of the experimental group in the thinking test. In light of the research results, the researcher showed some suggestions and recommendations for the purpose of conducting subsequent research and studies.
Keywords: Effect - Memory strength strategy - Deductive thinking.